CRISPR/CAS12A-BASED DIAGNOSTICS FOR COVID-19 - Kabylbayeva, A.; Zharylgassynova, K.; Abilova, A.; Amanzholova, M.; Abeldenov, S. (Eurasian Journal of Applied Biotechnology, 2021)
Access to fast and reliable methods for the detection of nucleic acids is critical in many different fields. Early identification of pathogens based on their genetic information associated with various diseases makes early diagnosis and treatment possible. The situation with the COVID-19 pandemic has shown that right now there is an urgent need to find enzymes for new diagnostic methods based on modern fundamental knowledge. Methods that allow covering a wider range of applications will be cheaper and do not require specialized premises, qualified personnel and will be simple to implement. One of these enzymes is the recently discovered endonuclease of the CRISPR/Cas systems - Cas12a. In this review, we provide a description of the Cas12a enzyme and its use in the COVID-19 diagnostics.